Nutritional Influences on Epigenetics, Aging and Disease - Anna Meiliana; Nurrani Mustika Dewi; Andi Wijaya (The Prodia Education and Research Institute (PERI), 2019)
BACKGROUND: Altered epigenetics is regarded to play quite a role in many chronic diseases including cancer, diabetes, obesity, dyslipidemia, hypertension and neurodegeneration, hence nutrition suggested to contribute in epigenetics and disease.CONTENT: Histone modifications, as a part of epigenetics mechanisms, depend on metabolites which acts as cofactors or substrates. Fluctuating levels of specific metabolites become the direct and rapid mechanisms to influence gene activity. Therefore, these metabolites may have a role as gatekeepers of chromatin, in chromatin landscape modulation as a response to key nutritional cues. Chemical modifications of histones and DNA have a critical role in epigenetic gene regulation including histone acetylation, and DNA methylation. Some enzymes add or remove such chemical modifications, and suggested to be sensitive to changes in intracellular metabolism, such as mutations in the metabolic enzymes succinate dehydrogenase (SDH), fumarate hydratase (FH) and isocitrate dehydrogenase (IDH) can result in cancer.SUMMARY: As a response to their nutrient environment, organisms tend to rapidly alter their gene expression. Many evidences showed an epigenetic regulation of chromatin is coupled to the changes on metabolites levels due to this kind of response. These metabolites will lead the recruitment of transcriptional regulatory complexes to DNA, thus clearly influencing the dynamic chromatin landscape.KEYWORDS: metabolites, enzymes, epigenetics, chromatin, nutrition